CRIMINAL ACTIONS PERFORMED BY NOTARY STAFF THAT OPEN CONFIDENTIALITY OF NOTARY POSITION - Murshal Sanjaya (International Journal of Social Science, 2021)
The role of the notary office administrative staff in maintaining the confidentiality of the deed according to the code of ethics and the oath of office of a notary. The role of the notary office administrative staff is part of the notary office organ that has a causal legal relationship that should act as a notary's obligation to maintain and keep the deed secret. Legal consequences The administrative staff of a notary office who does not maintain the confidentiality of the deed can be charged with the provisions of Article 322 paragraph (1) of the Criminal Code, whoever deliberately discloses a secret that must be kept because of his position or disbursement, both now and in the past, is threatened with a maximum imprisonment of nine months or a maximum fine of nine thousand rupiahs.